Les subalternes peuvent-elles parler? - Spivak, Gayatri Chakravorty..; Vidal, Jérôme.. (Éd. Amsterdam, 2009)
Dans le cadre d'un dialogue critique avec Michel Foucault, Gilles Deleuze et la tradition marxiste, G.C. Spivak articule le concept de subalterne (à ne pas confondre avec les notions de minoritaire ou d'opprimé) et s'interroge sur les femmes subalternes du tiers-monde, l'unification des subalternes au sein d'une communauté.
Keywords: approches et analyses; arts; care; com5170; corps; cours; discipline; féminisme décolonial; har4600; histoire et politique; incontournable; oui; premier cycle; thématiques; études littéraires; études postcoloniales

Décoloniser les représentations: esquisse d'une géographie culturelle de nos « Autres » - Hancock, Claire (Annales de géographie, 2008)
Cet article propose d’appliquer les méthodes et axes de réflexion de la géographie culturelle (analyse des discours et représentations, attention à la formation discursive d’identités socio-spatiales) à certains des enjeux de notre société post-coloniale, et notamment aux identités et territorialités contraintes qu’elle octroie aux populations dites « issues de l’immigration ». Il suggère également de reposer « au féminin » certaines des interrogations sur ces identités.
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; europe; féminisme décolonial; justice sociale; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; système colonial; systèmes d'oppressions; thématiques; violences

Les Principes De Jogjakarta: Principes sur l'application de la législation internationale des droits humains en matière dórientation sexuelle et d'identité de genre (2006)
Principes additionnels et obligations additionnelles des états au sujet de l’application du droit international des droits humains en matière d’orientation sexuelle, d’identité de genre, d’expression de genre et de caractéristiques sexuelles pour completer les Principes de Jogjakarta Depuis leur adoption en 2006, les Principes de Jogjakarta ont évolué pour devenir une déclaration faisant autorité sur les droits humains des personnes « d’orientations sexuelles et d’identités de genre diverses ». La dernière décennie a été témoin de développements significatifs dans le domaine du droit international des droits humains, ainsi que dans la compréhension des violations des droits humains subies par les personnes « d’orientations sexuelles et d’identités de genre diverses », et dans la reconnaissance des violations souvent distinctes touchant des personnes en raison de leur « expression de genre » ou de leurs « caractéristiques sexuelles ».Les Principes de Jogjakarta plus 10 (PJ+10) visent à documenter et à détailler ces développements à travers un ensemble de Principes additionnels et d’Obligations additionnelles des États.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; antiracisme; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; outils; pol4022; premier cycle; périodes historiques; queer; racisme; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis

Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Transformations : thinking through feminism, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". -- Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme